Exciton confinement in homo- and heteroepitaxial ZnO/Zn(1-x)Mg(x)O quantum wells with x < 0.1 - Laumer, Bernhard; Wassner, Thomas A.; Schuster, Fabian; Stutzmann, Martin; Schörmann, Jörg; Rohnke, Marcus; Chernikov, Alexej; Bornwasser, Verena; Koch, Martin; Chatterjee, Sangam; Eickhoff, Martin; Justus Liebig University Giessen (My University, 2011)
ZnO/Zn(1 - x)Mg(x)O single quantum well (SQW) structures with well widths d(W) between 1.1nm and 10.4 nm were grown by plasma-assisted molecular beam epitaxy both heteroepitaxially on c-plane sapphire and homoepitaxially on (000 (1) over bar)-oriented bulk ZnO. A significantly reduced Mg incorporation in the top barrier related to the generation of stacking faults is observed for heteroepitaxial samples. Exciton localization is observed for both types of samples, while an enhancement of the exciton binding energy compared to bulk ZnO is only found for homoepitaxial SQWs for 2nm <= d(W) <= 4 nm. Consistently, for homoepitaxial samples, the carrier dynamics are mainly governed by radiative recombination and carrier cooling processes at temperatures below 170 K, whereas thermally activated non-radiative recombination dominates in heteroepitaxial samples. The effects of polarization-induced electric fields are concealed for Mg concentrations x < 0.1 due to the reduction of the exciton binding energy, the screening by residual carriers as well as the asymmetric barrier structure in heteroepitaxial wells.
Keywords: ZnO/Zn(1-x)Mg(x)O; single quantum wells (SQW); homoepitaxial samples; heteroepitaxial samples; exciton binding energy; ddc:530